Análisis del proceso productivo en la Panadería Sabropan ubicada en la cuidad de Babahoyo - Briones Quinto, Axel Micheld (2021)
The main objective of this research work is to identify the problems raised in the sabropan bakery, which has caused related problems in their production processes. The methodology used for the present work consisted of conducting a field study which made it possible to identify the current situation of said premises, in addition to applying qualitative and quantitative methods reflected in interviews with personnel and consumer surveys. To identify the problems in the area, it was found that the use of the main work tools and the handling of the raw material is not adequate due to the lack of parameters where the processes to be followed are detailed; as well as an activity guide that serves as a reference for the correct elaboration of the product. Based on the study, a production plan was designed to help improve these problems based on strategic procedures that allow efficient control and optimization of resources.